2022
DOI: 10.1227/neu.0000000000002270
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Rich and Platelet-Rich Fibrin for Skull Base Reconstruction After Endoscopic Endonasal Skull Base Surgery

Abstract: BACKGROUND: Postoperative cerebrospinal fluid (CSF) leak is one of the most common complications after endoscopic endonasal approach to the skull base. OBJECTIVE: To analyze the effect of leukocyte-rich and platelet-rich fibrin (L-PRF) as part of a standardized endonasal skull base repair protocol on postoperative infection and CSF leak rate. METHODS: One hundred three patients who underwent an endoscopic endonasal approach and were reconstructed using a standard technique (Group A) were compared with 139 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…L-PRF was also reported to reduce postoperative CSF leak by 76% in cases with intraoperative CSF leak (relative risk 0.24, 95% CI 0.06-0.87) and by 73% of patients with high-ow leak (relative risk 0.27, 95% CI 0.07-0.99). In patients undergoing surgery for diagnoses other than adenomas, in 13.4% of patients who had standard reconstruction reported postoperative leak, whereas there was no report in the PRP group (p = 0.047) 20 . Rasmussen et al reported the feasibility and protocol of using L-PRP in the reconstruction of endoscopic approaches to the sellar region 36 .…”
Section: Prp For Anterior Skull Base Reconstructionmentioning
confidence: 92%
See 1 more Smart Citation
“…L-PRF was also reported to reduce postoperative CSF leak by 76% in cases with intraoperative CSF leak (relative risk 0.24, 95% CI 0.06-0.87) and by 73% of patients with high-ow leak (relative risk 0.27, 95% CI 0.07-0.99). In patients undergoing surgery for diagnoses other than adenomas, in 13.4% of patients who had standard reconstruction reported postoperative leak, whereas there was no report in the PRP group (p = 0.047) 20 . Rasmussen et al reported the feasibility and protocol of using L-PRP in the reconstruction of endoscopic approaches to the sellar region 36 .…”
Section: Prp For Anterior Skull Base Reconstructionmentioning
confidence: 92%
“…Due to the wound healing and adhesive properties, it has been used as a scaffolding layer for dural repair. Although it has not been widely used, initial studies are promising 19,20 . As prepared from the receiver's blood, its application has nearly no reported complications or adverse effects 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a recent RCT study by Constanzo et al, 103 patients who underwent an endoscopic endonasal approach and were reconstructed using a standard technique were compared with 139 patients using the same protocol with the addition of L-PRF, postoperative intracranial infection and CSF leak at 6 months. The researchers found that PRF reduced the rate of postoperative CSF leaks in patients with intraoperative leaks, without differences on postoperative meningitis [ 244 ].…”
Section: Use Of Plasma Rich With Platelets and Extracellular Vesicles...mentioning
confidence: 99%